2017
DOI: 10.1039/c7cp04310d
|View full text |Cite
|
Sign up to set email alerts
|

Cold atom–atom–ion three-body recombination of 4He–4He–X (X = H or D)

Abstract: The atom-atom-ion three-body recombination (TBR) of mixed He and X (X = H or D) systems is investigated by solving the Schrödinger equation using the adiabatic hyperspherical representation method. It is shown that the dominant products after a TBR in the ultracold limit (E ≤ 0.1 mK × k) are different for the two systems. For the HeHeH system, the rate of TBR into the HeH ion is nearly two orders of magnitude larger than that of TBR into the neutral He molecule. In contrast, the yield of He is a little higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In other words, reaction channel (2) is dominant for ion-atom-atom collisions. The preponderance of molecular ions as the final product state has been experimentally confirmed [85] and partially supported through full quantum mechanical calculations regarding the formation of molecular anions in some systems [86,87]. Therefore, it seems that our investigations at the cold regime may be extensible, under proper circumstances, to the ultracold realm.…”
Section: An Atomic Ion In a Bath Of Ultracold Atomssupporting
confidence: 55%
“…In other words, reaction channel (2) is dominant for ion-atom-atom collisions. The preponderance of molecular ions as the final product state has been experimentally confirmed [85] and partially supported through full quantum mechanical calculations regarding the formation of molecular anions in some systems [86,87]. Therefore, it seems that our investigations at the cold regime may be extensible, under proper circumstances, to the ultracold realm.…”
Section: An Atomic Ion In a Bath Of Ultracold Atomssupporting
confidence: 55%
“…When photogenerated electrons and holes migrate to the surface, they can drive different semi-reactions. [47] The extremely negative redox potential of electrons within these BC 2 N monolayers may efficiently overcome the overpotential and promote the charge transfer rate during the photocatalytic reduction process of CO 2 . [48,49] F I G U R E 5 Imaginary parts of dielectric constants of BC 2 N-α and BC 2 N-β, computed by HSE06 functionals…”
Section: Redox Capability Of the Potential Bc 2 N Photocatalystsmentioning
confidence: 99%
“…Quantum chemical calculations were carried out using DMol 3 package. The molecular structure was optimized to ensure the true minima on the potential energy surface.…”
Section: Theoretical Calculation Methodsmentioning
confidence: 99%
“…Herein, the weak peak at 535.6 eV was ascribed to the satellite peak of C]O structure, which well proved the presence of coumarin on the aluminum surface. 10 The peak at 531.4 eV showed the strongest intensity, which conformed to aluminum oxides/hydroxides, i.e., Al 2 O 3 and Al(OH) 3 . This revealed that the chemical composition of the corroded surface was predominated by Al 2 O 3 and Al(OH) 3 .…”
Section: Surface Elements and Chemical Statesmentioning
confidence: 97%
See 1 more Smart Citation